Alternatives to monetary disorder - Hirsch, Fred.; Doyle, Michael W.; Morse, Edward L. (New York : McGraw-Hill, 1977)
This book explore the nature of economic arrangements among nations and the relationship between the monetary system and other aspects of international politics.
Includes index.
Bibliography: p. 141-142.
usc 21/09/18
Loans
Keywords: International finance; International economic relations